2015
DOI: 10.1371/journal.pone.0122893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Glutamate and Aspartate on Diquat-Induced Oxidative Stress in Piglets

Abstract: This study aimed to investigate the protective effects of dietary glutamate and aspartate supplementations on diquat-induced oxidative stress in piglets. Diquat injection significantly reduced growth performance, including body weight, average daily weight gain, and feed intake (P<0.05). Meanwhile, diquat administration induced oxidative stress evidenced by the decreased serum nitric oxide (NO) and elevated malondialdeyhde (MDA) concentration (P<0.05). Furthermore, diquat-induced oxidative stress disrupted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 36 publications
12
123
1
Order By: Relevance
“…Intragastric or intraperitoneal administration of H 2 O 2 could decrease growth performance and caused oxidative stress [2123]. Furthermore, previous studies showed that addition of H 2 O 2 (300  μ M) to chicken intestinal epithelial cells for 24 h significantly decreased cell survival and SOD activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Intragastric or intraperitoneal administration of H 2 O 2 could decrease growth performance and caused oxidative stress [2123]. Furthermore, previous studies showed that addition of H 2 O 2 (300  μ M) to chicken intestinal epithelial cells for 24 h significantly decreased cell survival and SOD activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone-suppressed protein synthesis is alleviated by leucine Growing evidence suggests that dietary supplementation with AA confers beneficial effects on stress (Yin et al, 2015). As an essential BCAA, the metabolic roles for L-leucine go far beyond serving exclusively as a substrate for de novo protein synthesis.…”
Section: Mtor Inhibition May Be Involved In Dexamethasonesuppressed Pmentioning
confidence: 99%
“…This mucosal barrier function is impaired under conditions of oxidative stress brought about by excess reactive oxygen species (24). Diquat is widely used as an oxidant in in vitro or in vivo experiments to induce oxidative stress and apoptosis (25,26). Glutamate supplementation ameliorates endotoxin-induced damage to the jejunal epithelium and intestinal paracellular hyperpermeability (27,28), suggesting a critical role for Glu in intestinal-mucosal barrier function.…”
Section: Introductionmentioning
confidence: 99%